Transdermal delivery of fluorescein isothiocyanate-dextrans using the combination of microneedles and low-frequency sonophoresis - Boonnada Pamornpathomkul; Sureewan Duangjit; Suvida Laohapatarapant; Theerasak Rojanarata; Praneet Opanasopit; Tanasait Ngawhirunpat (Elsevier, 2015)
This study aimed to evaluate the patient-friendly methods that are used in the delivery of hydrophilic macromolecules into deep skin layers, in particular, the combination of microneedles patch (MNs patch) and low-frequency sonophoresis (SN). The hydrophilic macromolecule drug fluorescein isothiocyanate (FITC)-dextrans (FD-4: MW 4.4 kDa) was used as the model drug in our experimental design. In this study, excised porcine skin was used to investigate and optimize the key parameters that determine effective MNs- and SN-facilitated FD-4 delivery. In vitro skin permeation experiments revealed that the combination of MNs patch with SN had a superior enhancing effect of skin permeation for FD-4 compared to MNs alone, SN alone or untreated skin, respectively. The optimal parameters for the combination of MNs and SN included the following: 10 N insertion force of MNs, 4 W/cm2 SN intensity, 6 mm radiation diameter of the SN probe, 2 min application time, and the continuous mode duty cycle of SN. In addition, vertical sections of skin, clearly observed under a confocal microscope, confirmed that the combination of MNs and SN enhanced permeation of FD-4 into the deep skin layers. These studies suggest that the combination of MNs and SN techniques could have great potential in the delivery of hydrophilic macromolecules into deep skin.